AN ANALYSIS OF METAPHOR USED IN ADELE’S SONG - Imeldayanti Nehe; Dwina Putri Ayu Saragih; Nurhana Tri Rizqi; Mhd. Johan (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
This research aims to analyzed the types of metaphors and to analyzed the emotion of metaphor used in Adele's song. This research used the theory of Lakoff & Johnson (2003) and the theory of Kövecses (2010). In conducting this research, the researchers used 12 titles of Adele’s songs randomly as data source. This research used qualitative research method and in data analysis the researchers were identified, classified and interpreted. The result of this research was found 33 metaphors which divided into three types, there are 15 structural metaphor, 8 orientation metaphor and 9 ontology metaphor which separated into 3 types there were 3 entity, 3 container and 3 personifications. Moreover, the researchers found eight types of metaphor emotion in Adele’s songs, there were 7 emotion of anger, 1 emotion of happiness, 17 emotion of sadness, 6 emotion of love, 1 emotion of pride, Base on the analysis, the most frequently metaphors in the Adele’s songs are structural metaphor and the emotion of metaphor mostly used the metaphor of sadness.